Implementation of SDGs in Community Empowerment by an Islamic Philanthropic Institution - Abidin, Zaenal; Azman, Azlinda; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2025)
This study investigates the function of Islamic philanthropic organizations—specifically, the East Java Lazismu Representative Office—in promoting Sustainable Development Goals (SDGs) via community empowerment. This research used a qualitative case-study methodology to evaluate Lazismu's governance, operational issues, and program alignment with the Sustainable Development Goals, employing theoretical frameworks from Pierre Bourdieu and Jim Ife. Research indicates that Lazismu's community empowerment programs, organised around the pillars of education, health, social welfare, economic development, humanitarian efforts, and environmental sustainability, substantially advance SDG objectives, including poverty alleviation and the promotion of quality education. Nonetheless, implementation primarily retains a benevolent nature, demonstrating restricted participatory and transformative empowerment. Primary challenges encompass insufficient oversight, variable implementation of operating standards, and internal disputes concerning fund allocation. Despite Lazismu's strong social connections and collaboration among stakeholders, the empowerment process must incorporate greater community engagement and skill enhancement to foster enduring, self-sustaining growth within the community. The research emphasises prospects for augmenting effect via enhanced governance and participatory methodologies.